Patient as teacher sessions contextualize learning, enhancing knowledge, communication, and participation of pharmacy students in the United Kingdom - Andrew Martin Lunn; Ann Urmston; Steven Seymour; Andrea Manfrin (Journal of Educational Evaluation for Health Professions, 2020)
Purpose This study aimed to evaluate the impact of Patient as teacher (PAT) sessions on the knowledge, communication skills, and participation of pharmacy students in the United Kingdom. Methods During the academic year 2019–2020, year 1 and 2 pharmacy students at the University of Central Lancashire were invited to complete a questionnaire following PAT sessions. Data were analyzed by means of descriptive statistics, including mean and standard deviation for: continuous variables and reliability analysis. Pearson’s chi-square or Fisher exact test, odds ratio, and phi were used for analyzing dichotomous variables. Thematic analysis was used for free text comments. Results Sixty eight of 228 students participated (response rate of 29.8%). No statistical difference was found between gender (P=0.090); a statistically significant difference was found between year (P=0.008). Cronbach’s α (0.809) confirmed a good internal consistency. Ninety-seven percent of the students learned a lot, and 85.3% appreciated and valued the PAT sessions; 89.7% wanted more sessions. Ninety-two point seven percent perceived the sessions to contextualize their learning. Five questions were dichotomized by grouping the responses into negative and positive; 90.3% of responses were positive and did not show statistically significant differences in gender and year of study. Overall students’ free text comments were positive, but active listening and consultation appeared in the positive and negative domains, highlighting the need for more student engagement. Conclusion PAT sessions had a positive impact on students’ knowledge, communication skills and participation, and contextualized learning. They provide a valuable contribution to the pharmacy students’ experience in the United Kingdom.